Sanitizing food contact surfaces by the use of essential oils. (January 2019) - Falcó, I.; Verdeguer, M.; Aznar, R.; Sánchez, G.; Randazzo, W.
Abstract: Chemical sanitizers continue to be widely used by the food industry to disinfect food contact surfaces. However, as some chemical disinfectants have been reported to produce unhealthy by-products, alternative and natural compounds need to be investigated. To this end, nine essential oils (EOs) were screened to develop a natural sanitizing solution (SAN) for disinfecting food contact surfaces. Once extracted, their antimicrobial activity and chemical composition were determined. An exploratory multivariate approach was used to investigate the relationships between the chemical and microbiological data sets. Among the tested EOs, Thymbra capitata EO, containing up to 93.31% oxygenated monoterpenes (mainly carvacrol), showed the strongest antimicrobial activity and thus was assayed as a potential SAN for food contact surfaces. To this end, a SAN consisting of 1% T . capitata EO was first validated according to the AOAC standard, which showed about 8 log reduction for Escherichia coli and Salmonella enterica after 30 and 60 s of contact time, respectively. Then, the SAN was evaluated at various concentrations, cleanliness conditions, and contact times on stainless steel, glass, and polypropylene surfaces for sanitizing purposes. The results showed that the SAN containing 2.5% of T . capitata EO applied for 10 min, reduced the levels of E . coli by >3 log and S . enterica by 1 log under clean working conditions on the three tested surfaces. These findings indicate that EOs can be used as natural disinfectants to decontaminate food contact surfaces, thus lowering the risk of the indirect transfer of bacterial pathogens to food or persons. Highlights: Nine essential oils (EOs) were screened for antibacterial activity and chemical composition. Thymbra capitata EO shows high antimicrobial activity. T. capitata EO-based natural sanitizing solution (SAN) was validated according to AOAC 960.09 standard. SAN was effective against Escherichia coli for food contact surfaces disinfection according to EN 13697:2015. SAN represents a natural sanitizing solution for cleaning steel, glass and plastic food contact surfaces.